Perceived Usefulness and Ease of Use of Online Examination System: A Case of Institute of Accountancy Arusha - Semlambo, Adam; Almasi, Kabeya; Liechuka, Yusuph (International Journal of Scientific Research and Management (IJSRM), 2022)
Online examination systems have revolutionised the learning process for many learning institutions around the globe, especially in developing countries, and have proven effective during the COVID-19 pandemic to maintain social distance. This study employed the Technological Acceptance Model (TAM) to evaluate the perceived usefulness and ease of use of such systems when adopted in developing countries like Tanzania, where such systems are not well known by the learners. Also, the perceptions of such examinations among learners are not well explored. The Institute of Accountancy in Arusha was used as a case study where the population was 125, which is all third-year undergraduate learners of computer-based subjects. A descriptive analysis through SPSS version 26 showed a mixed perception about supporting online examinations in higher learning institutions. Furthermore, the study analysed different factors for perceived usefulness and ease of use of online examinations for learners, such as participant technical consigns, academic contributions, and security consigns. Based on the findings, the study recommended that the institution's management support is needed, and dedicated funds should be set aside to support reliable technologies for online learning and examinations.